The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1080/19768354.2012.696553
|View full text |Cite
|
Sign up to set email alerts
|

Gallotannin regulates apoptosis and COX-2 expression via Akt and p38kinase pathway in human lung cancer cell line, A549

Abstract: Gallotannin (GT) is derived from plant poly phenol and is associated with biological actions in a wide range of cells. In this study, we evaluated the effect of GT on apoptosis and cyclooxygenase-2 (COX-2) expression and attempted to shed light on the mechanism of action in A549 human lung carcinoma cells. We found that GT dramatically induced apoptosis as demonstrated by expression of p53 and active caspase-3 via western blot analysis and fragmented DNA as detected by DNA fragmentation and DAPI staining. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
(42 reference statements)
2
5
0
Order By: Relevance
“…Previous studies have also indicated the role of benzo(a)pyrene dihydrodiol epoxide, a byproduct of BAP, in the regulation of cell survival through microRNA-29a [71]. In line with our observations, treatment with nicotine was found to increase the clonogenic potential of various cancer cells [72,73]. In addition, silencing of Akt1 and 2 decreased the clonogenic efficiency of untreated and tobacco-treated cells.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies have also indicated the role of benzo(a)pyrene dihydrodiol epoxide, a byproduct of BAP, in the regulation of cell survival through microRNA-29a [71]. In line with our observations, treatment with nicotine was found to increase the clonogenic potential of various cancer cells [72,73]. In addition, silencing of Akt1 and 2 decreased the clonogenic efficiency of untreated and tobacco-treated cells.…”
Section: Discussionsupporting
confidence: 90%
“…Many previous studies have suggested the importance of Cox-2 in other cancers such as cancers of colorectal, breast, prostate, and blood. Moreover, in endometrial and lung cancer, Cox-2 was reported to be a downstream target of Akt and plays a significant role in the regulation of apoptosis of cancer cells [72,90,115,116]. In our study, we observed that the knockdown of both Akt1 and 2 isoforms led to the reduction of Cox-2 protein expression.…”
Section: Discussionsupporting
confidence: 62%
“…In addition, previous studies showed that gallotannin prevented nephrolithiasis via suppression of calcium oxalate crystal binding and oxalate induced oxidative stress in renal epithelial cells 14 . Though gallatonnin showed the proapoptotic actions in colon cancer cells 15 and lung cancer cells A549 16 , underlying anti-cancer mechanism of gallotannin in hepatocellular carcinoma still remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In liver cancer HepG2 hepatocellular carcinoma cell line, GT attenuated the expression of pro-caspase9, pro-caspase3, Bcl2, and integrin β1 and cleaved poly(ADP)ribose polymerase [68]. Gallotannin dramatically induced apoptosis through the expression of p53 and active caspase-3 and fragmented DNA in A549 human lung carcinoma cells [69]. In DU145, PC-3, and M2182 prostate cancer cell lines, the inhibition of Mcl-1 and activation of caspases were critically involved in GTinduced apoptosis [70].…”
Section: Gallotannin and Apoptosismentioning
confidence: 95%